2009
DOI: 10.1152/ajpheart.00092.2009
|View full text |Cite
|
Sign up to set email alerts
|

Altered reactivity to norepinephrine through COX-2 induction by vascular injury in hypercholesterolemic rabbits

Abstract: Although long-term use of cyclooxygenase (COX)-2 inhibitors may be associated with increased cardiovascular risk, their effects on vascular reactivity in atherosclerosis has remained largely unexplored. The aim of the present study was to evaluate the role of COX-2 induced by an atherosclerotic process, in the local control of vascular tone. New Zealand White rabbits were fed 0.3% cholesterol and subjected to balloon injury of the abdominal aorta. After 2 wk, the aorta was removed and used for organ bath exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…In agreement with this hypothesis, we noticed a significant reduction in plasma nitrite and nitrate levels in AngII-infused mice. A reduced phenylephrine-induced aortic contraction was reported in hypercholesteremic rabbits in association with an alteration of the cyclooxygenase (COX) signalling pathway [26]. In this study, plasma cholesterol level was not different between the AngII- and vehicle- infused mice, minimizing the possibility that the observed responses were mediated by hypercholesteremia-altered COX signalling.…”
Section: Discussionmentioning
confidence: 70%
“…In agreement with this hypothesis, we noticed a significant reduction in plasma nitrite and nitrate levels in AngII-infused mice. A reduced phenylephrine-induced aortic contraction was reported in hypercholesteremic rabbits in association with an alteration of the cyclooxygenase (COX) signalling pathway [26]. In this study, plasma cholesterol level was not different between the AngII- and vehicle- infused mice, minimizing the possibility that the observed responses were mediated by hypercholesteremia-altered COX signalling.…”
Section: Discussionmentioning
confidence: 70%
“…In addition, the release of endogenous TXA 2 acting on TP receptors altered the vasoconstriction induced by other mediators , suggesting a role of local TXA 2 release in the modulation of vascular tone. Although TXA 2 is not the major prostanoid released from experimentally injured abdominal aortas from cholesterol‐fed rabbits, norepinephrine caused decreased responses in these vessels, which were reversed with COX inhibitors . Although this study did not specifically address the role of TP receptor, a previous study showed that rabbits lacking TP receptor exhibited decreased phenylephrine‐induced vasoconstriction compared with wild‐type rabbits, only when fed a high cholesterol diet .…”
Section: Vascular Inflammationmentioning
confidence: 82%
“…International Journal of Cardiology 184 (2015) [559][560][561][562][563][564][565][566][567] In addition, selective deletion of COX-2 in mice was reported to induce interstitial and perivascular fibrosis with an enhanced susceptibility to induced arrhythmias [16]. On the other hand, celecoxib has several ionic channel effects and interferes with the cardiovascular electrophysiology [12,17].…”
Section: Introductionmentioning
confidence: 99%